Prunus - Vicente, Ariel Roberto; Crisosto, Carlos H.; Manganaris, George A. (My University, 2011)
The main bioactive compounds (carotenoids, ascorbic acid, vitamin E, phenolic compounds, proanthocyanidins and tannins), phytonutrients, factors affecting bioactive compounds (genetic factors, cultural practices and environmental conditions, and storage and processing) of Prunus species are discussed. This book collectively discusses and reviews empirical data on health-promoting properties of major fresh produce types. It provides detailed information on identity, nature, bioavailablity, chemopreventative effects and postharvest stability of specific chemical classes with known bioactive properties. In addition, chapters discuss the various methodologies for extraction, isolation, characterisation and quantification of bioactive compounds and the in vitro and in vivo anticancer assays. This book is an essential resource for researchers and students in food science, nutrition and fruit and vegetable production.
Keywords: Fruits; Prunus; Vegetables; Health promotion; Antioxidants; Agriculture